Penentuan Waktu Proses Pembuatan Kain dengan Pendekatan Cross-Case pada Industri Tekstil - Evan Nugraha; Rini Mulyani Sari (Universitas Winaya Mukti, 2018)
PT. X was a company engaged in weaving cotton production. Many types of cotton consisted of type 185, type 186, type 188 and type 189. Nevertheless, there were still many problems in the operational production of the weaving department. One of them was the length in processing time of the weaving section that could affect the next process. Based on a literature review, it showed that lean method could be implemented in process industry even it was not entirely. The method that usually used in the process industry was the cross-case method. A case study was a method that chosen in conducting this research by forming propositions first. There were two products selected as the case study: cotton 188 and cotton 189. This research consisted of two steps. The first step was the measurement of operational performance before implementing the lean method. The second step was cross-case analysis by synchronizing between the empirical data and the propositions. The lean method would increase the accuracy of product delivery. It had been proven by reduction of the cycle time of both products ranges from 18,5% to 31,5%. The cross-case method could be applied with the Kanban, the set-up time reduction and forming the pull system in the production floor.